Influence of Climate Change Communication on Responsible Environmental Behaviour among Residents of Niger State - Ngene, Andrew Hyacinth (Informasi, 2025)
Effective communication strategies can increase public awareness and understanding of climate change, leading to behavioural changes that support environmental sustainability. However, how climate change communication has influenced responsible environmental behaviour among residents of Niger state has largely remained uncertain. The study was guided by four research objectives with survey as the method of enquiry, while the questionnaire served as the instrument for data collection. Taro Yamane (1964) statistical formula was used to arrive at a sample size of 400 respondents derived from the study population, while the theory of reasoned action (TRA) served as the theoretical framework. Findings revealed high level of awareness and knowledge of climate change communications among residents of Niger state with radio and public campaigns identified to have played crucial roles in disseminating climate change information. The study concluded that, diverse communication channels and appropriate framing techniques should be utilized to not only create awareness about climate change effects, but to also drive people to act to maintain a sustainable environment. It was recommended among other things that climate change messages should be disseminated utilising both the conventional and social media to educate and inform a more diverse and heterogeneous audience. Keywords: Assessment, Health Communication, Immunization, Strategies, Women